Estimation of ship manoeuvring characteristics in the conceptual design stage - Mainal, Mohd. Ramzan; Kamil, Mohd. Salim (Faculty of Mechanical Engineering, 1996)
In relation to the problems of the maritime safety, the diversification in ship types or the growth in ship sizes has enhanced the significance of manoeuvrability as one of the fundamental performances of ships. Namely it has become very important to predict the ship manoeuvrability at the stage of the initial ship design process. This paper presents a mathematical model for estimating the ship manoeuvring performance to cope with the increasing demands for conceptual design stage evaluation of safety in ship operation. The mathematical model developed can be extended further to be made applicable to various other problems such as low speed manoeuvres, lateral shifting stopping manoeuvres.